STRATEGIES OF ENGLISH STUDENTS DEPARTEMENT IN BUILDING CHARACTER THROUGHT POETRY - Imroatul Azizah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This article presents the strategies of English students department of Islamic University of Malang in building character through poetry. Poetry is one type of literary works besides short stories and novel. The objective of this study was to describe the learning strategies used by English students department of sixth semester to build character through poetry. In conducting the study, the researcher uses the Descriptive Qualitative approach. The subjects of this study were 15 English students department. The data were collected through doing online questionnaire, online interview, and documentation that was due in January 17th to April 21th, 2021. The data were analyzed using Qomariyah theory (2020) of code types. There are developing and applying codes, identifying themes, and summarizing the data. According to the findings, students use writing, listening, and or reading a poetry as their strategies to build their character and also the students mention in online interview that by reading a poetry someone can understand and feel what the author wrote. The findings of this study are likely to be beneficial for the future researcher who had read this study, can learn the strategies in building character through poetry are used writing, listening, and or reading poetry. The researcher really suggests that the next research on finding the strategies in building character through poetry will use the newest parameters found by other researcher other than those who have mention above.Key Words: Poetry, Strategies, Character